Psychometric Properties of the Spanish Version of the Complex Postformal Thought Questionnaire: Developmental Pattern and Significance and Its Relationship With Cognitive and Personality Measures - Contreras, Antonio; Suárez Falcón, Juan C.; Caprara, Mariagiovanna; Pozo, Pilar; Gómez Veiga, Isabel; Cabras, Emilia (My University, 2023)
Postformal thought is the highest state of thinking in adults, extending beyond formal operations. Sinnott¿s Complex Postformal Thought Questionnaire (PFTQ) is one of the most widely used measures of this construct and thus, the main aim of this study was to translate a Spanish version of the PFTQ and to validate it using a sample of 1093 subjects aged from 18 to 71 years. A cross-validation study was carried out and measurement invariance was analyzed by gender and across age groups: emerging adults, 18-29 years; established adults, 30-45 years; and middle-aged adults, 46-60 years. Furthermore, evidence of validity was assessed relative to cognitive and personality measures (i.e.: mindfulness, grit, resilience, intolerance of uncertainty, conscientiousness, metacognition and learning strategies), as was the developmental pattern of the PFTQ. In the cross-validation study, both the exploratory and confirmatory factor analyses indicated it was appropriate to consider a unidimensional structure. Likewise, the PFTQ exhibited good psychometric properties (¿ = .84; ¿ = .83), and there was reasonable evidence of strict invariance by gender and across age groups. Moreover, the PFTQ was significantly and positively related to metacognition, learning strategies, mindfulness, conscientiousness, resilience and grit, whereas it was significantly and negatively related to intolerance of uncertainty, albeit to a lesser extent. Finally, a developmental progression of the PFTQ was observed during adulthood, with significant differences observed between the latent means of the three age groups, which was associated with moderate effect sizes between the emerging and the established or middle-age adult groups (d = 0.28 and d = 0.37, respectively). By contrast, a very small and practically negligible effect size was detected between the established and middle-aged adult groups (d = 0.09). Relativistic operations would appear to underlie psychosocial development in established adulthood, when they are most needed. Overall, the Spanish version of the PFTQ showed good psychometric properties and validity evidence of its utility to studying adult thinking.